Influence of prior comorbidities and chronic medications use on the risk of COVID-19 in adults: a population-based cohort study in Tarragona, Spain - Vila-Córcoles, Angel; Ochoa-Gondar, Olga; Satué-Gracia, Eva M.; Torrente-Fraga, Cristina; Gomez-Bertomeu, Frederic; Vila-Rovira, Angel; Hospital-Guardiola, Immaculada; de Diego-Cabanes, Cinta; Bejarano-Romero, Ferran; Basora-Gallisà, Josep (BMJ open, 2020)
ObjectiveTo investigate possible relationships between pre-existing medical conditions (including common comorbidities and chronic medications) and risk for suffering COVID-19 disease in middle-aged and older adults.DesignPopulation-based retrospective cohort study.SettingTwelve primary care centres (PCCs) in Tarragona (Spain).Participants79 083 people (77 676 community-dwelling and 1407 nursing-home residents), who were all individuals aged >50 years affiliated to the 12 participating PCCs.OutcomesBaseline cohort characteristics (age, sex, vaccinations, comorbidities and chronic medications) were established at study start (1st. March 2020) and primary outcome was time to COVID-19 confirmed by PCR among cohort members throughout the epidemic period (from 1st. March 2020 to 23rd. May 2020). Risk for suffering COVID-19 was evaluated by Cox regression, estimating multivariable HRs adjusted for age, sex, comorbidities and medications use.ResultsDuring the study period, 2324 cohort members were PCR-tested, with 1944 negative and 380 positive results, which means an incidence of 480.5 PCR-confirmed COVID-19 cases per 100 000 persons-period. Assessing the total study cohort, only age (HR 1.02; 95% CI 1.01 to 1.03; p=0.002), nursing-home residence (HR 21.83; 95% CI 16.66 to 28.61; p<0.001) and receiving diuretics (HR 1.35; 95% CI 1.04 to 1.76; p=0.026) appeared independently associated with increased risk. Smoking (HR 0.62; 95% CI 0.41 to 0.93; p=0.022), ACE inhibitors (HR 0.68; 95% CI 0.47 to 0.99; p=0.046) and antihistamine (HR 0.47; 95% CI 0.22 to 1.01; p=0.052) were associated with a lower risk. Among community-dwelling individuals, cancer (HR 1.52; 95% CI 1.03 to 2.24; p=0.035), chronic respiratory disease (HR 1.82; 95% CI 1.08 to 3.07; p=0.025) and cardiac disease (HR 1.53; 95% CI 1.06 to 2.19; p=0.021) emerged to be also associated with an increased risk. Receiving ACE inhibitors (HR 0.66; 95% CI 0.44 to 0.99; p=0.046) and influenza vaccination (HR 0.63; 95% CI 0.44 to 0.91; p=0.012) was associated with decreased risk.ConclusionAge, nursing-home residence and multiple comorbidities appear predisposing for COVID-19. Conversely, receiving ACE inhibitors, antihistamine and influenza vaccination could be protective, which should be closely investigated in further studies specifically focused on these concerns.